2018
DOI: 10.1080/02650487.2018.1454703
|View full text |Cite
|
Sign up to set email alerts
|

How advertising in offline media drives reach of and engagement with brands on Facebook

Abstract: Research investigating the drivers of consumers' engagement with brands on social media is proliferating. However, little is known about how advertising outside social media drives engagement with brands on social media. This study aims to explore the relation between advertising spend in different offline media (TV, radio, newspapers, magazines, out of home), and reach of and engagement with brand pages on Facebook. The study uses a unique real-life data-set containing information about the Facebook pages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…Existing research has mainly focused on sales. Although this focus on sales is in line with the media agencies' expectations about social selling, future studies should also focus on the role of social media in different stages of the decision process, such as need recognition, awareness, consideration, and evaluation (e.g., see Batra and Keller 2016;Voorveld et al 2016). Finally, because social media are often used simultaneously with other media, future research on the effects of media multitasking with social media is important.…”
Section: Research On the Integration Of Social Media In The Media MIXmentioning
confidence: 89%
See 2 more Smart Citations
“…Existing research has mainly focused on sales. Although this focus on sales is in line with the media agencies' expectations about social selling, future studies should also focus on the role of social media in different stages of the decision process, such as need recognition, awareness, consideration, and evaluation (e.g., see Batra and Keller 2016;Voorveld et al 2016). Finally, because social media are often used simultaneously with other media, future research on the effects of media multitasking with social media is important.…”
Section: Research On the Integration Of Social Media In The Media MIXmentioning
confidence: 89%
“…Another relevant challenge with regard to channel characteristics of social media is that in a brand communication program, social media are usually not used as a stand-alone activity but are combined with other media. In addition, consumers more often than not use social media in combination with other digital and traditional media in their consumer journey (Kannan and Li 2017;Voorveld, Araujo, et al 2018).…”
Section: Channel Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding which CBBE dimensions translate into more (or less) engagement behaviors allows brand managers to single out the relevant customer mindset metrics that require their attention (Petersen et al 2018). As for instance, advertising that pushes these metrics can subsequently drive online brand engagement (de Vries, Gensler, and Leeflang 2017;Voorveld et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Socialbreakers, a social media analytics company, conducted an analysis of 5,000 Facebook brand and media pages in 2015 and found that post shares strongly correlate with reached individuals in the cases of both media and brand pages on Facebook (Socialbakers, 2015). Albeit the scarcity of research regarding the role of reached individuals on user engagement, recent research indicates a significant drop in terms of organic and viral reach on Facebook in recent years on brand pages (Voorveld, Araujo, Bernritter, Rietberg, & Vliegenthart, 2018). Furthermore, Voorveld et al (2018) found that paid reach in the form of advertising and the number of post likes were the most substantial influencing factors of organic reach on Facebook; however, paid advertising on websites outside of Facebook do not contribute to higher activity on the analysed social media platform.…”
Section: Theoretical Backgroundmentioning
confidence: 99%